Morphology of porous glasses. Colloid-chemical aspect - Antropova, Tatiana (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
A summarizing of the results of complex study of pore morphology of porous glasses has been carried out taking into consideration the dissolved secondary silica state in the systems alkali borosilicate glass – a leaching solution. An influence of the composition and phase structure of an initial glass, and their leaching conditions, on the colloid-chemical characteristics of the porous glasses has been shown. The polymodal micro porous substructure and meso porous one, the size and a form of the pores and secondary silica particles as well as the fractal dimensions of their aggregates, the coefficients of structural resistance and tortuosity of the pores has been discussed.
Optica Applicata, Vol. 38, 2008, nr 1, s. 5-16
Keywords: optyka; phase-separated glass; porous glass; structure; porosimetry; transmission electron microscopy; small angle X-ray scattering